Partial Sperm beta1 Integrin Subunit Deletion Proves Its Involvement in Mouse Gamete Adhesion/Fusion - Barraud-Lange, Virginie (Int J Mol Sci, 2020)
We have previously shown, using antibodies, that the sperm alpha6beta1 integrin is involved in mouse gamete fusion in vitro. Here we report the conditional knockdown of the sperm Itgb1 gene. It induced a drastic failure of sperm fusogenic ability with sperm accumulation in the perivitelline space of in vitro inseminated oocytes deleted or not for the Itgb1 gene. These data demonstrate that sperm, but not oocyte, beta1 integrin subunit is involved in gamete adhesion/fusion. Curiously, knockdown males were fertile in vivo probably because of the incomplete Cre-mediated deletion of the sperm Itgb1 floxed gene. Indeed, this was shown by Western blot analysis and confirmed by both the viability and litter size of pups obtained by mating partially sperm Itgb1 deleted males with females producing completely deleted Itgb1 oocytes. Because of the total peri-implantation lethality of Itgb1 deletion in mice, we assume that sperm that escaped the Itgb1 excision seemed to be preferentially used to fertilize in vivo. Here, we showed for the first time that the deletion, even partial, of the sperm Itgb1 gene makes the sperm unable to normally fertilize oocytes. However, to elucidate the question of the essentiality of its role during fertilization, further investigations using a mouse expressing a recombinase more effective in male germ cells are necessary.